Vitamin D Deficiency in Iraqi Women with Hashimoto Thyroiditis - Kalaweesh Ali Mohamed; Sahlah Khorshid Abbas (Tikrit Journal of Pure Science, 2025)
One kind of autoimmune thyroid disease is Hashimoto's thyroiditis (HT), which is more frequent in women than in males. The purpose of our study was to demonstrate any possible variations in vitamin D levels between ladies with HT and healthy women.